Experiential Learning of Unschooled Adults: knowledge and learning contexts - Cavaco, Carmen (2016)
This article is the product of a qualitative research based on biographical interviews, aiming to analyze the process of experiential learning of unschooled adults. Our study analyzed the learning process used by these adults throughout their lives, what they learned, which contexts and people were significant in this process. We followed the theoretical framework based on experiential learning and life stories. We believe that this training process is very broad and entails life experiences. This research revealed that unschooled adults have a diverse and multidimensional knowledge as a result of the experiential learning process consistently used throughout their lives.